High Glucose Suppresses Keratinocyte Migration Through the Inhibition of p38 MAPK/Autophagy Pathway - Li, Lingfei; Zhang, Junhui; Zhang, Qiong; Zhang, Dongxia; Xiang, Fei; Jia, Jiezhi; Wei, Ping; Zhang, Jiaping; Hu, Jiongyu; Huang, Yuesheng (Frontiers in Physiology, 2019)
Wound healing is delayed frequently in patients with diabetes. Proper keratinocyte migration is an essential step during re-epithelialization. Impaired keratinocyte migration is a critical underlying factor responsible for the delayed wound healing in patients with diabetes, which is mainly attributed to the hyperglycemic state. However, the underlying mechanisms remain largely unknown. Previously, we demonstrated a marked activation of p38/MAPK pathway in the regenerated migrating epidermis, which in turn promoted keratinocyte migration. In the present study, we find that p38/MAPK pathway is downregulated and accompanied by inactivation of autophagy under high glucose environment. In addition, we demonstrate that inactivation of p38/MAPK and autophagy result in the inhibition of keratinocyte migration under high glucose environment, and the activating p38/MAPK by MKK6(Glu) overexpression rescues cell migration through an autophagy-dependent way. Moreover, diabetic wound epidermis shows a significant inhibition of p38/MAPK and autophagy. Targeting these dysfunctions may provide novel therapeutic approaches